Factors Influencing the Delay in Negative Conversion of PCR Swab Test Results in Patients with COVID-19: Factors Influencing the Delay in Negative Conversion of PCR Swab Test Results in Patients with COVID-19 - Nurkholis, Fathur; Hanang Wibisono, Banteng; Suryanto, Agus; Handoyo, Thomas; Farida, Farida; Tanamas, Jimmy (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background : The negative conversion duration of SARS-CoV-2 RNA was related to disease progression, and a prolonged negative conversion could provide early warning signal for poor prognosis in patients with COVID-19. The objectives of this study was to identify the factors influencing the delay in negative conversion of PCR swab test results in patients with COVID-19 as a consideration in determining the COVID-19 prevention policy in the community Methods : A retrospective cross-sectional study involving 68 patients diagnosed with COVID-19 that was treated in Dr. Kariadi General Hospital Medical Center Semarang from June 1st to December 30th 2020. Negative conversion was evaluated based on the results of the RT-PCR swab test on day 7, 14 and 21. Results : Mean negative conversion time for all patients was 11.63±5.08 days. Thirty-one factors were evaluated in the initial univariate Cox and Kaplan-Meier analysis. Older age (>59 years), overweight (>25 kg/m2), fever (>38°C), shortness of breath, diabetes mellitus, neutrophilia, hypoalbuminemia, CRP and antiviral treatment showed significant association with negative conversion time. These factors were then included in a multivariate regression analysis. Hypoalbuminemia or albumin level of <3.0 g/dL was found as an independent factor associated with negative conversion time of viral RNA (HR:1.986; 95%CI:1.098–3.594), and hypoalbuminemia was presumed to cause prolonged viral clearance time in patients with COVID-19. Conclusion : The factors influencing the prolong in negative conversion of viral RNA in patients with COVID-19 were older age, overweight, fever, shortness of breath, diabetes mellitus, neutrophilia, hypoalbuminemia, CRP and antiviral treatment. Hypoalbuminemia was an independent predictor for prolonged negative conversion of viral RNA in patients with COVID-19.